Muhammad Quraish Shihab wa Ārā’uhu al-Fiqhiyyah - Jamil, Fathurrahman (Studia Islamika, 1999)
The Qur'an is believed by Muslims as the most important source of Islamic teachings. Legal matters (ahkam),which are part of (or earn the most important aspect of) Islam, must also be one of the concerns of the Qur'an. But does it mean that a mufassir (exegete), since he also has the deal with the legal verses, is automatically a legal expert? In order to answer that question, the writer of this article justifiably did two of the following steps. First, he chose a mufassir as d case study; second, be decided to put forward a set of legal issues and to see that the chosen mufassir had to say about them. The mufassir that he chose is Quraish Shihab, one of Indonesian scholars who was a director of IAIN Jakarta. As for the legal problems, the writer chose to discuss the follouring: qat'iy-zhanniy (absolute-relative [meaning of the Qur'anic verses]), naskh-mansukh (the abrogating-abrogated verses), and the role of the prophetic tradition vis-a-vis the Qur'an.DOI: 10.15408/sdi.v6i2.734